Whole genome sequencing and function prediction of 133 gut anaerobes isolated from chicken caecum in pure cultures - Medvecky, Matej; Cejkova, Darina; Polansky, Ondrej; Karasova, Daniela; Kubasova, Tereza; Cizek, Alois; Rychlik, Ivan (BMC genomics, 2018)
BACKGROUND: In order to start to understand the function of individual members of gut microbiota, we cultured, sequenced and analysed bacterial anaerobes from chicken caecum. RESULTS: Altogether 204 isolates from chicken caecum were obtained in pure cultures using Wilkins-Chalgren anaerobe agar and anaerobic growth conditions. Genomes of all the isolates were determined using the NextSeq platform and subjected to bioinformatic analysis. Among 204 sequenced isolates we identified 133 different strains belonging to seven different phyla - Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria, Verrucomicrobia, Elusimicrobia and Synergistetes. Genome sizes ranged from 1.51 Mb in Elusimicrobium minutum to 6.70 Mb in Bacteroides ovatus. Clustering based on the presence of protein coding genes showed that isolates from phyla Proteobacteria, Verrucomicrobia, Elusimicrobia and Synergistetes did not cluster with the remaining isolates. Firmicutes split into families Lactobacillaceae, Enterococcaceae, Veillonellaceae and order Clostridiales from which the Clostridium perfringens isolates formed a distinct sub-cluster. All Bacteroidetes isolates formed a separate cluster showing similar genetic composition in all isolates but distinct from the rest of the gut anaerobes. The majority of Actinobacteria clustered closely together except for the representatives of genus Gordonibacter showing that the genome of this genus differs from the rest of Actinobacteria sequenced in this study. Representatives of Bacteroidetes commonly encoded proteins (collagenase, hemagglutinin, hemolysin, hyaluronidase, heparinases, chondroitinase, mucin-desulfating sulfatase or glutamate decarboxylase) that may enable them to interact with their host. Aerotolerance was recorded in Akkermansia and Cloacibacillus and was also common among representatives of Bacteroidetes. On the other hand, Elusimicrobium and the majority of Clostridiales were highly sensitive to air exposure despite their potential for spore formation. CONCLUSIONS: Major gut microbiota members utilise different strategies for gut colonisation. High oxygen sensitivity of Firmicutes may explain their commonly reported decrease after oxidative burst during gut inflammation.
Keywords: sekvenování celého genomu; kur domácí; Genome Size; Anaerobe; Propionate; Metabolic pathway; délka genomu; fylogeneze; Chickens; High-Throughput Nucleotide Sequencing; Whole genome sequencing; Phylogeny; cékum; Gastrointestinal Microbiome; Chicken; Microbiota; Cecum; střevní mikroflóra; DNA, Bacterial; anaerobní bakterie; DNA bakterií; Animals; Bacteria, Anaerobic; zvířata; vysoce účinné nukleotidové sekvenování; Host-microbiota interactions; Butyrate; Microbiome; Whole Genome Sequencing